2022
DOI: 10.1039/d1ta10920k
|View full text |Cite
|
Sign up to set email alerts
|

The growth mechanism of lithium dendrites and its coupling to mechanical stress

Abstract: Operando high-resolution light microscopy with extended depth of field is used to observe large regions of an electrode during electrodeposition of lithium. The analysis of the morphology of the evolving...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…This result can be verified indirectly by the experimental results of Rafiz et al 41 who demonstrated that high tortuosity of the separator is effective in preventing dendrite propagation. Kink formation during electrodeposition was reported by Becherer et al 59 using scanning electron microscopy images. When γ = 1 (the pores are not shielded), there are multiple dendrite growth points on the surface of the Li metal; however, owing to the existence of the SM, the transmission path of Li ions is changed significantly, and only the dendrite growth points corresponding to vertically unobstructed pores will eventually grow into dendrites.…”
Section: Influence Of the Degree Of Staggered Overlapmentioning
confidence: 75%
See 3 more Smart Citations
“…This result can be verified indirectly by the experimental results of Rafiz et al 41 who demonstrated that high tortuosity of the separator is effective in preventing dendrite propagation. Kink formation during electrodeposition was reported by Becherer et al 59 using scanning electron microscopy images. When γ = 1 (the pores are not shielded), there are multiple dendrite growth points on the surface of the Li metal; however, owing to the existence of the SM, the transmission path of Li ions is changed significantly, and only the dendrite growth points corresponding to vertically unobstructed pores will eventually grow into dendrites.…”
Section: Influence Of the Degree Of Staggered Overlapmentioning
confidence: 75%
“…This result can be verified indirectly by the experimental results of Rafiz et al who demonstrated that high tortuosity of the separator is effective in preventing dendrite propagation. Kink formation during electrodeposition was reported by Becherer et al . using scanning electron microscopy images.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both effects lead to capacity loss and are enhanced with increasingly irregular, nonplanar, and high-surface-area structures of the lithium anode. Experiments have found that the nonplanar structure arises from whiskers, growing with no apparent growth direction during charging. Lithium whiskers, often with small diameters, entangle each other to form mossy lithium . The growth process is not limited by electrolyte transport at battery-typical current densities. During discharging, portions of lithium remain isolated in the SEI shell. ,, This isolated lithium can accumulate at the electrode, increasing the cell resistance because the ion path becomes tortuous or floats in the electrolyte and possibly reacts at high voltage and elevated temperatures .…”
mentioning
confidence: 99%